PENERAPAN RATIONAL EMOTIVE BEHAVIOR THERAPY (REBT) UNTUK MENINGKATKAN PSYCHOLOGICAL WELL-BEING PADA PENDERITA EPILEPSI GRANDMAL - Mutiara Mirah Yunita (Psibernetika, 2016)
Epilepsy is the physical illness in many years that have biological, psychological, sociological and spiritual aspect that have impact in individual quality life. Future of patient with epilepsy illness is being determined from psychological condition, in particular in psychological well-being conditions. Patient with epilepsy grandmal often have emotional disorder. They can not accept her or himself, high anxiety, break down feeling, depression, helpless feeling, shame feeling, sadness, dependent, not confident, and defendant feeling, so that emotion negative was have difficult to grow up in self-actualization. The psychology well-being is condition who someone have accept her or himself, accept the past memories, grow up, have a meaning life, positive relation with people, have capacity of managing self, confident to deciding whatever something best. Enhancement of psychology well-being is being done by rational emotive behaviour therapy (REBT) which is a technique to straighten irrationally minded that create emotionally disorder. This research use qualitative (in- depth interview, observation) and psychological test. Besides that, questionnaire, pre-test, and post-test. Subject in this research is woman, 21 years old who has epilepsy grandmal illness in the low psychological well-being condition. She has  average IQ and emotional disorder. The intervention is being done in tenth. According result by questionnaire data, the intervention has be done is positive result. It has enhancement of  psychological well-being for subject who epilepsy grandmal. Those are changes behaviour that expected in subject. Keywords : psychological well-being; grandmal epilepsy; rational emotive behavior therapy